Sustainability of Shrimp Farming in Sarawak: A Case Study of Asajaya, Samarahan Division, Sarawak - Lee, Nyanti; Lau, S.; Ling, T. V.; Gerald, T. L. S.; Chan, C. L. (Universiti Malaysia Sarawak, 2013)
Shrimp farming is a relatively new industry in Sarawak. In many of the major shrimp producing countries, the sustainability of this industry is threatened due to poor management practices, pollution from ponds effluent and outbreak of viral diseases. The objectives of this study were to characterize and quantify effluent from shrimp ponds and identify some of the issues related to the sustainability of this industry in Sarawak. Data were obtained from the Department of Agriculture, Natural Resources and EIlvironment Board Sarawak and field sampling at Asajaya. The results of this study indicate that shrimp farms discharged large amount of orthophosphate, nitrate-nitrogen, arnmonianitrogen, biochemical oxygen demand and total suspended solids into the adjacent water body. This has resulted in the decline of the river water quality. Sarawak aquaculture industry must learn from the negative experiences of other shrimp producer countries because economic sustainability in shrimp farming cannot be achieved without environmental sustainability.